2018
DOI: 10.1093/bioinformatics/bty427
|View full text |Cite
|
Sign up to set email alerts
|

MODE-TASK: large-scale protein motion tools

Abstract: SummaryMODE-TASK, a novel and versatile software suite, comprises Principal Component Analysis, Multidimensional Scaling, and t-Distributed Stochastic Neighbor Embedding techniques using Molecular Dynamics trajectories. MODE-TASK also includes a Normal Mode Analysis tool based on Anisotropic Network Model so as to provide a variety of ways to analyse and compare large-scale motions of protein complexes for which long MD simulations are prohibitive. Beside the command line function, a GUI has been developed as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…The collective motions of the protein-membrane-water systems were analysed by extracting the top principal components (PCs) using the GROMACS utility toolkits applied to the main-chain atoms, and MODE-TASK. 85 We performed singular value decomposition PCA on alpha carbons (1355 atoms for C83 and 1363 for Notch100) for both systems, and the trajectories were prepared by removing periodicity and water molecules. The lipid binding occupancy was determined using VMD.…”
Section: Dynamic Trajectory Analysismentioning
confidence: 99%
“…The collective motions of the protein-membrane-water systems were analysed by extracting the top principal components (PCs) using the GROMACS utility toolkits applied to the main-chain atoms, and MODE-TASK. 85 We performed singular value decomposition PCA on alpha carbons (1355 atoms for C83 and 1363 for Notch100) for both systems, and the trajectories were prepared by removing periodicity and water molecules. The lipid binding occupancy was determined using VMD.…”
Section: Dynamic Trajectory Analysismentioning
confidence: 99%
“…In contrast, non-degenerate modes characterize unique directions of motions that often capture global meaningful motions that account for large conformational changes. Previous studies showed that dominant conformational changes of complexes were captured within the slowest non-degenerate modes (Atilgan et al, 2001;Chennubhotla et al, 2005;Shrivastava and Bahar, 2006;Wako and Endo, 2011;Isin et al, 2012;Lee et al, 2017;Ross et al, 2018). Here, we identified eight non-degenerate modes of PTPS.…”
Section: Resultsmentioning
confidence: 77%
“…NMA was predominantly performed using the MODE-TASK tool suite (Ross et al, 2018) which employs the ANM (Atilgan et al, 2001) to construct an ENM of the protein structure. Although the ANM has been described previously (Atilgan et al, 2001), we provide a summary here.…”
Section: Calculation Of the Normal Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all springs are in a relaxed state in the network, no energy minimization is required, in comparison to normal mode analysis in which an expensive initial energy minimization is required prior to calculating the Hessian matrix. For large biomolecules and multi-protein complexes, ENM models with a resolution lower than standard have been used ( Durand et al, 1994 ; Doruker et al, 2002 ; Chennubhotla et al, 2005 ; Ahmed and Gohlke, 2006 ; Kurkcuoglu et al, 2009 ; Ross C. et al, 2018 ). The gross representation of large assemblies has proven to predict dynamics of the rigid and flexible parts of the proteins ( Ross C.J.…”
Section: Introductionmentioning
confidence: 99%